Comparative effectiveness study of patient‐reported outcomes after proton therapy or intensity‐modulated radiotherapy for prostate cancer. Issue 7 (30th December 2013) - Hoppe, Bradford S.; Michalski, Jeff M.; Mendenhall, Nancy P.; Morris, Christopher G.; Henderson, Randal H.; Nichols, Romaine C.; Mendenhall, William M.; Williams, Christopher R.; Regan, Meredith M.; Chipman, Jonathan J.; Crociani, Catrina M.; Sandler, Howard M.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Data continue to emerge on the relative merits of different treatment modalities for prostate cancer. The objective of this study was to compare patient‐reported quality‐of‐life (QOL) outcomes after proton therapy (PT) and intensity‐modulated radiation therapy (IMRT) for prostate cancer. METHODS A comparison was performed of prospectively collected QOL data using the Expanded Prostate Cancer Index Composite (EPIC) questionnaire. QOL data were collected during the first 2 years after treatment for men who received PT and IMRT. PT was delivered to 1243 men at a single center at doses from 76 grays (Gy) to 82 Gy. IMRT was delivered to 204 men who were included in the Prostate Cancer Outcomes and Satisfaction with Treatment Quality Assessment (PROSTQA) study in doses from 75.6 Gy to 79.4 Gy. The Wilcoxon rank‐sum test was used to compare EPIC outcomes by modality using baseline‐adjusted scores at different time points. Individual questions were assessed by converting to binary outcomes and testing with generalized estimating equations. RESULTS No differences were observed in summary score changes for bowel, urinary incontinence, urinary irritative/obstructive, and sexual domains between the 2 cohorts. However, more men who received IMRT reported moderate/big problems with rectal urgency (P = 0.02) and frequent bowel movements (P = 0.05) than men who received PT. CONCLUSIONS There were no differences in QOL summary scores between the IMRT and PT cohorts during early follow‐up (up to 2‐years). Response to individual questions suggests possible differences in specific bowel symptoms between the 2 cohorts. These outcomes highlight the need for further comparative studies of PT and IMRT. Cancer 2014;120:1076–1082. © 2013 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society.